Leadership in physical education: Systematic review of the last five years - Novri Gazali; Norazlinda Saad; Romi Cendra; Syed Kamaruzaman; Ripa'i Ripa'i (Universitas Nusantara PGRI Kediri, 2022)
Leadership has been identified as an important factor that may help guide and contribute to the effective provision of physical education in several different contexts. Despite the importance attributed to physical education leadership, more empirical research evidence still needs to relate to the topic. The purpose of this review is to describe leadership research in physical education in the last five years (2018-2022). Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) were adopted for the research review, and two databases (Scopus and Web of Science) were used in article browsing. 741 articles were obtained from two databases (Scopus: 392 articles) and (WoS: 349 articles). After following the exclusion criteria, only 13 articles remained. The review succeeded in showing that Iraq publishes the most research, and quantitative, qualitative, mixed research (quantitative and qualitative) approaches, and heuristic approaches are the methods and types of research used, and then the review is divided into five research groups: (i) physical education teacher leadership, (ii) principals and departmental leadership, (iii) student leadership, (iv) school leadership, and (v) cultural leadership. Of these five groups, transformational leadership is the most frequently discussed topic. Future research can be continued with mapping analysis of research on this topic using bibliometric or scientometric studies. This literature review can also be continued by discussing the topic of leadership in sports.